Understanding Manitoba Inuit’s Social Programs Utilization and Needs: Methodological Innovations - Lavoie, Josée G.; McDonnell, Leah; Nickel, Nathan; Clark, Wayne; Anawak, Caroline; Anawak, Jack; Brown, Levinia; Clark, Grace; Evaluardjuk-Palmer, Maata; Ford, Frederick; Dutton, Rachel; Katz, Alan; et al. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
Manitoba is home to approximately 1,500 Inuit, and sees 16,000 consults yearly from the Kivalliq region of Nunavut to access services. The purpose of our study was to develop detailed profiles of Inuit accessing services in Manitoba, by using administrative data routinely collected by Manitoban agencies, to support the development of Inuit-centric services. This study was conducted in partnership with the Manitoba Inuit Association, and Inuit Elders from Nunavut and Manitoba. Findings shows that the Inuit community living in Manitoba is fairly stable, with only approximately 5 percent of Inuit moving in and out of Manitoba on any given year. Inuit settle primarily in Winnipeg, and a significant proportion depend on social programs such as Income Assistance and housing support. A significant number of Inuit children have contact with the Child Welfare System. Our results support the need for more Inuit-centric programming, including family support and language programs.